Abstracts book: Intentions: Conversations, Experiences and Knowledge (Estudos em Design, 2019)
RCA School of Communication Research Work in Progress AbstractsA diverse group of emerging communication researchers present their work-in-progress at Westworks in White City. Through a variety of activities – workshops, screenings, exhibits, talks, they will convey the intentions underlying their investigations, which are posited around three interconnected threads: conversation, experience and knowledge. Introduction by Teal Triggs ExhibitorsConversationsKaren BosySinead EvansVicky KimHotessa LaurencePaul RansomWelmoet WartenaExperiencesGesi AnFarah KadhumPaul DJ MoodyLarissa NowickiSimon PicardKelly SpanouRimjhim SuranaKnowledgeWenbo AiMallaa AlamoudiKollontai Cossich DinizFernando GaldonEmily HoongSarah Kirby-GinnsCristina PortugalPatricia PuertasCaroline Ward